A comparative analysis of CT scan versus diagnostic nasal endoscopy in chronic rhino sinusitis - Pullarat, Ahamed Nauphal; Kottayil, Shakeeber; Raj, Girish; N. K., Basheer (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: With the advent of nasal endoscopy (DNE) and computed tomography (CT) in the evaluation of patients with chronic rhinosinusitis, it has popularized the functional endoscopic sinus surgery. The objective of this study is to find out effectiveness and limitations of CT and DNE in chronic rhinosinusitis. Methods: Patients attending the Otorhinolaryngology outpatient department of MES medical college with chronic rhinosinusitis (CRS), who satisfy the inclusion criteria, were included in the study. They were given a course of antibiotics and antihistamines for a period of 10 days prior to CT Nose & PNS followed by an interval of 5 days nasal endoscopy done and findings were compared. Results: In this study, 58% cases were males and 42% females, most common symptom was a headache (76%). In DNE 82% cases had septal deviation and 86% in CT scan. Most common sinus cavity involved in CT scan was maxillary sinus. Conclusions: CT scan has got a better advantage compared to DNE in detecting the anatomical variations as well as to know the condition of the sinus cavity and the extent of disease in sinuses. In conditions like middle meatal secretions, mucosal change, polyp DNE gave a better picture of the condition. Both DNE and CT scan are complementary to each other in CRS.